# Solve for z 7/11*(z-4)-27/11=-5 711⋅(z-4)-2711=-5
Simplify 711⋅(z-4)-2711.
Simplify each term.
Apply the distributive property.
711z+711⋅-4-2711=-5
Combine 711 and z.
7z11+711⋅-4-2711=-5
Multiply 711⋅-4.
Combine 711 and -4.
7z11+7⋅-411-2711=-5
Multiply 7 by -4.
7z11+-2811-2711=-5
7z11+-2811-2711=-5
Move the negative in front of the fraction.
7z11-2811-2711=-5
7z11-2811-2711=-5
Combine fractions.
Combine fractions with similar denominators.
7z-28-2711=-5
Subtract 27 from -28.
7z-5511=-5
7z-5511=-5
7z-5511=-5
Multiply both sides of the equation by 11.
7z-55=-5⋅11
Remove parentheses.
7z-55=-5⋅11
Multiply -5 by 11.
7z-55=-55
Move all terms not containing z to the right side of the equation.
Add 55 to both sides of the equation.
7z=-55+55
Add -55 and 55.
7z=0
7z=0
Divide each term by 7 and simplify.
Divide each term in 7z=0 by 7.
7z7=07
Cancel the common factor of 7.
Cancel the common factor.
7z7=07
Divide z by 1.
z=07
z=07
Divide 0 by 7.
z=0
z=0
Solve for z 7/11*(z-4)-27/11=-5

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top